Earnings Management and Dividend Policy: Empirical Evidence from Major Sectors of Pakistan - Ahmed, Farhan; Advani, Neha; Kanwal, Sahabia (International Journal of Economics and Financial Issues, 2018)
This paper means to inspect the relationship between Price earning (P/E) ratio as a proxy of earning management and dividend payout proportion. This paper utilizes multivariate analysis using 10 years annual data from 2006 to 2016. It delivers new confirmation demonstrating that when the return on equity is more prominent than the required rate of return, the P/E ratio and dividend payout ratio shows a negative relationship and positive convexity or vice versa. This study helps the corporate superintendents and stock financial experts to focus on decreasing payout ratio than the increasing payout ratio. No past review has handled the issue of the contingent relationship between P/E proportion and payout proportion in Pakistani Industry and specifically on Fertilizers, Cement, Food and Oil & Gas sectors. Keywords: Dividend Per Share, Price Earnings Ratio, Returns on Equity, Earning per share JEL Classifications: C10, G12, G35